2018
DOI: 10.1371/journal.pone.0192904
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic effect of Pichia pastoris X-33 produced in parboiled rice effluent and YPD medium on broiler chickens

Abstract: In a previous paper we showed that the yeast Pichia pastoris X-33 grown in parboiled rice effluent supplemented with glycerol byproduct from the biodiesel industry improved the quality of the effluent. In this paper we show the validation of this yeast (PPE) as probiotic for broilers. Its effect on feed efficiency and immunomodulation was compared with the same yeast grown in yeast peptone dextrose medium (PPY), with Saccharomyces boulardii (SBY) and with the controls fed unsupplemented feed (CON). One-day-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
3
2
0
Order By: Relevance
“…In this study, no negative effects of P. pastoris were observed on the analyzed parameters, nor any lesion was found in the liver or intestine, regardless of the medium in which the yeast was cultured. These data highlight the innocuous profile of P. pastoris , reinforcing previous results in broilers and mice 2022 . A prior study indicated that the residual biomass of black tea production, composed of Pichia sp.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In this study, no negative effects of P. pastoris were observed on the analyzed parameters, nor any lesion was found in the liver or intestine, regardless of the medium in which the yeast was cultured. These data highlight the innocuous profile of P. pastoris , reinforcing previous results in broilers and mice 2022 . A prior study indicated that the residual biomass of black tea production, composed of Pichia sp.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, Gil de los Santos et al . 22 confirmed the immunomodulatory activity of P. pastoris produced in this same effluent, which generated in broilers, a higher anti-Gumboro antibodies titer than the control at 28 days. The same author had already demonstrated the potential of P. pastoris X-33 as a bioremediator microorganism, finding that the yeast grown in parboiled rice effluent supplemented with 15 g.L −1 of biodiesel glycerol promoted reductions in COD - chemical oxygen demand (55%), phosphorus (52%), and nitrogen (45%) 23 .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The low cytotoxicity toward mammalian cells and exceptional specificity of thanatin toward bacterial membranes [22] provide beneficial features for the development of thanatin-based biocontrol agents. Although the probiotic features of P. pastoris were not extensively studied, there are several reports speculating their probable application as probiotics [45] and highlighting their safety [46]. Here, we combined the high potential of yeast bioengineering with the exceptional antimicrobial activity of thanatin, associated with low toxicity, to broaden the arsenal of designer biocontrol agents and provide new AMP applications.…”
Section: Discussionmentioning
confidence: 99%